The effect of training and supervision of the head room on the performance of executive nurse room hospital surgical, hospital Tk. II Pelamonia Makassar - Abdul Majid; Amar Sani (STIE AMKOP, 2016)
BSTRACT The effect of training and supervision of the head room on the performance of executive nurse room hospital surgical, hospital Tk. II Pelamonia Makassar (supervised by Hasmin and A. Ikhsan Kadir). The aim of this study is to assess and analyze : (1). The Influence of training towards performance (2). The Influence of supervision towards performance (3). The effect of training and supervision towards supervision. This research use primary data with population number of 115 nurse at hospital, the survey was conducted from November to December 2016. The data were analyzed using descriptive statistical analysis. The results of the research indicate : (1) There is influence of training towards performance (2) There is influence of supervision towards performance (3) There are influence of training and supervision towards performance Key Word : Training, Supervision, and Performance